Discrimination perceived by patients being monitored for COVID-19. Tajamar Regalado, Ecuador - Melba Esperanza Narváez Jaramillo; Cinthya Lizeth Pantoja Narváez; Julio Rodrigo Morillo Cano; Sara Ximena Guerrón Enríquez (Medisur)
Foundation: COVID-19 had an impact on the population’ biopsychosocial state. Among attitudes and behaviors, discrimination manifested itself as one of the responses to different levels of personal and social interrelation. Objective: to describe the discrimination perceived by patients being monitored for COVID-19. Methods: descriptive and cross-sectional study, carried out from September 2021 to February 2022, in all patients monitored for COVID-19 (N=89) who live in Tajamar Regalado neighborhood (Tulcán, Ecuador). Through the survey, information was obtained on the variables: type of institution where they received medical follow-up, perception of discrimination, social support and community support. Results: 60.67% of patients reported that they almost always regretted having been infected with COVID-19; 59.55%, who always felt they were discriminated against for having suffered from the disease; 40.45%, who almost always considered it important to use protective measures to avoid further infections in their community; 48.31% stated that they almost always received counseling from health personnel; and 59.55% considered that their mental health was affected. Almost half of the patients expressed having received very bad social support, and 51.68% received bad social support from the authorities in particular. Conclusions: during the COVID-19 pandemic, there was social rejection of infected patients, which caused effects on their mental health. A lack of support from the community and authorities was evident; and little counseling by health personnel.